Analysis of pre-test failures and bond-strengths of seven adhesive systems to bovine dentine: A nine-year novice/beginner operator study. Issue 11 (November 2018) - Franz, A.; Lettner, S.; Watts, D.C.; Graf, A.; Moritz, A.; Schedle, A.
Abstract: Objective: The aims were to evaluate, via multi-year student cohorts: (i) the incidence of pre-test failures and (ii) shear bond strengths of single- and multi-step adhesives to bovine dentin. Methods: The experiments were performed by cohorts of dental students (2008–2016). Each year the bond strengths of three dental adhesives to bovine dentin were tested. Four self-etching adhesives (Optibond-All-in-One, [OBAIO]; Optibond XTR [OBXTR]); Xeno V [XV]; Xeno V+ [XV+]; a three-step etch-and-rinse-system (Optibond FL, [OBFL]), a self-etch universal adhesive (Scotchbond Universal [SBU]) and a self-etch/etch-and-rinse adhesive (Xeno Select, [XS]) were included in the study. Composite-cylinders were bonded perpendicularly to prepared bovine dentin surfaces. Shear-tests were performed with a universal-testing-machine. Results: Both overall, and within years, XV and XV+ showed significantly (p < 0.01) higher percentages of pre-test failures versus other adhesive systems tested in the period 2008–2014 (OAIO, OBFL, OBXTR). Fewest pre-test failures were observed for OBFL, OBXTR and SBU. Trends in mean bond strengths and Weibull distributions were noted, per adhesive, with trends in the incidence of pre-test failures. Pre-test-failures and bond strengths depended on the air-drying technique. The adhesive systems showed variable technique sensitivity. Multistep bonding systems (Optibond FL and Optibond XTR) showed minimal pre-test failures and high bond strength applied by relatively inexperienced operators and irrespective of the applied air-drying technique. However, two single-step adhesives (OAIO and SBU) showed comparable results to the multi-step systems. Significance: The clinical need for rapid application dentine adhesives can result in varied outcomes with relatively inexperienced operators. These outcomes include both the incidence of pre-test failures as well as the distributions of shear bond strengths achieved, although these measures appear to be related. However, both outcomes are dependent upon the adhesive products utilised and especially upon the applied air pressure (flow rate). Some rapid application systems appear to perform comparably with well-established multi-step adhesives.